1985
DOI: 10.1128/jcm.22.6.1025-1029.1985
|View full text |Cite
|
Sign up to set email alerts
|

Association of slime with pathogenicity of coagulase-negative staphylococci causing nosocomial septicemia

Abstract: To assess the role of slime in the pathogenesis of nosocomial bloodstream infections caused by coagulase-negative staphylococci, we compared the characteristics of 27 nosocomial bloodstream isolates with those of 27 skin isolates from non-hospital personnel. Of 27 bloodstream isolates, 14 were judged to be significant by a clinical index, and 13 were contaminants. Slime production was observed in 13 of 14 significant isolates but in only 3 of 13 contaminants (P = 0.0003) and 4 of 27 skin isolates (P = 0.0001).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0
7

Year Published

1990
1990
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(79 citation statements)
references
References 34 publications
3
69
0
7
Order By: Relevance
“…Clinical evaluations, studies of retrieved implants, and in vitro studies have suggested that bacterial adherence to the biomaterial is an important step in the development of infection (1,10,15-17J9). Much of the investigation on infection and bacterial adherence has focused on the use of Staphylococcus epidermidzs and polymeric catheter materials and has revealed that the propensity of the organism to stick to these materials is associated with their pathogenicity (7,9,11,23,26,27,33,37,40,43). The analysis of infection and the adherence pattern of the S. epidermidis that was isolated has shown this relationship, with reports of as much as 81% of the infections due to staphylococci, which are adherent organisms.…”
mentioning
confidence: 99%
“…Clinical evaluations, studies of retrieved implants, and in vitro studies have suggested that bacterial adherence to the biomaterial is an important step in the development of infection (1,10,15-17J9). Much of the investigation on infection and bacterial adherence has focused on the use of Staphylococcus epidermidzs and polymeric catheter materials and has revealed that the propensity of the organism to stick to these materials is associated with their pathogenicity (7,9,11,23,26,27,33,37,40,43). The analysis of infection and the adherence pattern of the S. epidermidis that was isolated has shown this relationship, with reports of as much as 81% of the infections due to staphylococci, which are adherent organisms.…”
mentioning
confidence: 99%
“…Ludwicka et al [27] quantitated the adherent bacteria by measuring the amount of total ATP (using a bioluminescence technique) present in bacteria adhering to pieces of a synthetic polymer. Ishak et al [28] immersed Teflon catheter segments in a bacterial suspension for 30 min, which were then rolled on blood agar plates. The number of colonies cultured after incubation for 18 h was proportional to the number of 'adherent' bacteria.…”
Section: Methods Of Recognising and Measuring Adherence / Slimementioning
confidence: 99%
“…This slimy substance protects bacteria against host defense mechanisms and antimicrobial agents [10]. Many other biological activities have been attributed to slime [11]. Slime is an extensive and diffuse polyanionic matrix that surrounds the cells [10].…”
Section: B a C T E R I A -B I O M A T E R I A L I N T E R A C T I O Nmentioning
confidence: 99%